1985
DOI: 10.2307/40285320
|View full text |Cite
|
Sign up to set email alerts
|

Pitch and Duration as Determinants of Musical Space

Abstract: In an experiment aimed at assessing dimensional properties of musical space, musicians rated the similarity of pairs of brief melodies on a 9-point scale. From our review of previous work, we hypothesized (1) that pitch variables would be considered more important than time or rhythmic variables by our subjects and (2) that the metrical consonance of pitch and duration patterns would generate a factor related to pattern regularity in listeners' musical space. Four melodies and their inversions were played in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
5

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 37 publications
5
103
5
Order By: Relevance
“…Peretz [29] reported that two right hemisphere damaged patients showed a selective deficit in the processing of pitch, while a reverse pattern of selective deficit of the temporal dimension was found in two left brain damaged patients. Other single case studies have also demonstrated selective impairment of one or the other dimension [13,24,30,31], and other studies in the field of cognitive psychology support the hypothesis of independence [15,26,28].…”
Section: Introductionmentioning
confidence: 71%
“…Peretz [29] reported that two right hemisphere damaged patients showed a selective deficit in the processing of pitch, while a reverse pattern of selective deficit of the temporal dimension was found in two left brain damaged patients. Other single case studies have also demonstrated selective impairment of one or the other dimension [13,24,30,31], and other studies in the field of cognitive psychology support the hypothesis of independence [15,26,28].…”
Section: Introductionmentioning
confidence: 71%
“…These findings were obtained with tasks involving either very long-term memory (Halpern, 1984) or more perceptual discriminations, such as similarity ratings for pairs of musical segments (Monahan & Carterette, 1985;Monahan, Kendall, & Carterette, 1987) and phrase completion (Palmer & Krumhansl, 1987a, 1987b. Thus, task factors cannot easily account for the discrepancy between this set of studies, on the one hand, and that supporting the single-component model, on the other.…”
Section: Downloaded By [Archives and Bibliothèques De L'ulb] At 05:44 1mentioning
confidence: 77%
“…In fact, there is only one article that touches on this issue (Monahan & Carterette, 1985). These authors found that five dimensions best explained similarity ratings of 32 melodies; the first three reflected temporal characteristics, and the last two were pitch-based.…”
Section: Introductionmentioning
confidence: 99%